Cover Image, Volume 57, Number 4, April 2022. Issue 4 (28th March 2022) - Adaikalam, Stephanie A.; Higano, Nara S.; Hysinger, Erik B.; Bates, Alister J.; Fleck, Robert J.; Schapiro, Andrew H.; House, Melissa A.; Nathan, Amy T.; Ahlfeld, Shawn K.; Brady, Jennifer M.; Woods, Jason C.; Kingma, Paul S.
Abstract : Back Cover Caption : The cover image is based on the Original Article Tracheostomy prediction model in neonatal bronchopulmonary dysplasia via lung and airway MRI by Stephanie A. Adaikalam et al., https://doi.org/10.1002/ppul.25905 . Image Credit: Cincinnati Children's Hospital Medical Center. [Correction added on 26 March 2022, after first online publication: This additional cover was added to this issue.]